Pengaruh Motivasi, Komunikasi dan Budaya Organisasi terhadap Kinerja Karyawan - Eni Erwantiningsih (Jurnal Manajemen dan Kewirausahaan, 2019)
The purpose of this research is to analyze the influence of motivation, communication and organizational culture  to employee performance. The object of  this study is Merdeka University Pasuruan. Data  collected through questionnaires given to 42 respondents of educational staff taken by census method.       The  results     show that: 1) motivatian has a significant effect on  employee performance, 2) communication does not have a significant effect on  employee performanc,e 3) organizational culture has a significant effect  on  employee performance, and 4) organizational culture has a  dominant effect on employee performance.https://doi.org/10.26905/jmdk.v7i2.3247